PENGARUH MOTIVASI, KOMPENSASI MELALUI KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Fatmawati, Alvina Puspha; Hidayat, Wahyu; Dewi, Reni Shinta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
The company in achieving a business activity which do need labor factors therein. Issues pertaining to labor is a low performance. Factors that can influence the occurrence of performance is the motivation, job satisfaction, stress level, physical condition, occupation, compensation system and economic aspects. The problem in this study was the occurrence of a decrease in employee performance and increase employee absenteeism arriving late, forgetful, and leave early . This study aims to determine the effect of motivation ( X1 ) compensation (X2 ) on job satisfaction ( Z ) on employee performance ( Y ) PT. Pelindo Semarang . Type eksplanatory research study used by all employees is still working in PT .Pelindo Semarang totaling 113 people. As for using census sampling technique . Data collection techniques in this study using interviews and questionnaires . Data analysis techniques used to test the validity, reliability testing, simple linear regression, multiple linear regression, path analysis, t test and F test with the aid of SPSS 16.0. Based on the results of the analysis show motivation, compensation and job satisfaction has an influence on employee performance. Advice that can be given in this study for variable compensation is that health insurance companies provide cash and cash overtime with timely enterprises have been determined previously, to give some sort of enterprise motivation variable intensive and ongoing training , seminars on the theme of work motivation , and make controlling the employees about the performance of each employee who has performed and occasionally provide some sort of direction ( briefing ) directly to each employee who has a low performance going forward is expected to reduce the level to make mistakes and grow and increase employee initiative to complete the job on time.